(untitled) (American Journal of Pedagogical and Educational Research, 2023)
This article gives information about psychoanalytic method, its origin, its significance in literature. An overview of this article will help in your understanding of psychoanalytic theory. A part from this, it discusses the psychoanalysis of “Jennie Gerhardt” by Theodore Dreiser.